Track segments in hadronic showers in a highly granular scintillator-steel hadron calorimeter - Adloff, Catherine; Briggl, Konrad; Eckert, Patrick; Harion, Tobias; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer (Journal of Instrumentation, 2013)
We investigate the three dimensional substructure of hadronic showers in the CALICE scintillator-steel hadronic calorimeter. The high granularity of the detector is used to find track segments of minimum ionising particles within hadronic showers, providing sensitivity to the spatial structure and the details of secondary particle production in hadronic cascades. The multiplicity, length and angular distribution of identified track segments are compared to GEANT4 simulations with several different shower models. Track segments also provide the possibility for in-situ calibration of highly granular calorimeters.
Gesehen am 06.05.2021